Aplikasi Manajemen Barang Reject Berbasis Android (Studi Kasus PT. Schneider Electric Manufacturing Batam) - Muhammad Nashrullah; Niken Aprilia Harefa (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
PT. Schneider Electric is leading the Digital Transformation of Energy Management and Automation in Homes, Buildings, Data Centers, Infrastructure and Industries. PT. Schneider is one of the companies that applies the technology applied to the work process, one of the Debug Manager systems, which is a system used to reject items in the line area, but it still has weakness in inputting product data when it read by users with a small text its make debug manager or LI (Line Inspector) often entered the wrong data, and there is no procedure that allows the debugging process of items that refuse to do research on the existing system. The research conducted at PT. Schneider Electric Manufacturing Batam was conducted to repair the Debug Manager system in PT. Schneider, this research was conducted with the waterfall method starting with conducting interviews with the operator or LI (Line Inspector) Debug Manager then proceeding with the application design (Design) which is then implemented, verified until maintenance is carried out. Reject Management Application based on android, which is an application that scans QR code on labels, and text that uses products on a smartphone or tablet and can also give debugging technicians notification. The debugging process can be done well.